A General Solution for the Governing Bending Equation - Moore, II (Engineering Journal, 1985)
The allowable bending stress Fb for most wide-flange sections is governed only by AISC Eq. 1.5-7, and Eq. 1.5-6 never need to be checked for these sections. Those wideflange sections for which Fb is determined by Eq. 1.5-6, and the unbraced lengths for which these forms govern, are easily identified by simultaneous solution of the bending equations for the common roots of length for any given yield stress Fy and bending coefficient Cb. Tables of these sections and a general solution for determining the governing bending equation are presented in this paper. The tables are useful supplements to Stockwells simplification of the bending equations and to Burgett and Tides extension of the use of the beam charts to designs with bending coefficients greater than unity. The tables and their use are presented in the body of this paper; simultaneous solutions of the bending equations for common roots of length are given in the appendix.